Religiusitas Komunitas Muslim di Media Sosial - Farhan (Asy-Syari’ah : Jurnal Hukum Islam, 2019)
Abstract: This research reveals about the religious culture of Muslim community alike the Qur'an in overcoming the anxiety of the soul because it is caused by the guide of social media. This continues to be done because it can be a problem solving in balancing the experience of ritual worship as well as social worship. This research, including the study of virtual ethnography and using the phenomenology approach and based on the foundation of communication science, especially the study of media related siber.Object field in question is an online field in social media Whatsapp, scout group sanggar more than 100 members, two administrators as a resource. The research question is how the implementation of al-Qur'an khataman among the alumni community of Sunan Ampel Boy Scouts in social media whatsapp June-July 2017 ?. The results showed that (1) Implementation khilmil Quran recitations conducted based on community resilience, sustainable and created atmosphere of religiosity. (2) Citizens of cyber can increase emotional, solidarity, among fellow Muslim communities realize the concept of amar ma'ruf. (3) The community entrusts administrators by dividing community members into two groups. Each group consists of 30 residents read in a week. (4) The constraints faced by community members are discussed and the solution is solved by musyarawah-mufakat in social media. (5) Administration of the recitation of the Quran documentary Quran orderly documentary cyber. Keywords: Religious Culture, Online Community, Social Media, Amar Ma'ruf